Conversational Implicature in Raya and The Last Dragon Movie Directed by Don Hall and Carloz López Estrada - Tauchid, Ahmad; Rosyita, Fina Ainur; Ramadhan, Deni (English Education and Literature Journal (E-Jou), 2023)
Linguistics is divided into two categories: macro linguistics and micro linguistics. Macro linguistics is divided into three categories: psycholinguistics, neurolinguistics, and ethnography. Micro linguistics is divided into several categories, including morphology, phonetics, phonology, syntax, semantics, sociolinguistics, and pragmatics. The goal of this study is to discover and analyze the many types of conversational implicature and maxim violations in Raya and The Last Dragon. Don Hall and Carloz López Estrada directed Raya and The Last Dragon, which was released in 2021. The descriptive qualitative method was employed to perform this research. The authors used Yule's theory (1996) to examine the different types of conversational implicature and the maxim of politeness. In cooperative principles, there are four maxims and two types of conversational implicature. The findings of this study show that: (1) In Raya and The Last Dragon, there are two types of conversational implicature; generic and particularized. Generalized conversational implicature is the most common type of conversational implicature seen in Raya and The Last Dragon. (2) There are six maxims as seen in Raya and The Last Dragon: maxim of wisdom, award, generacy, sympathy, consensus, and humility. The maxim of award is the most common maxim in Raya and The Last Dragon. Keywords: Conversational Implicature, Maxim, Movie